Invitro Antioxidant Effects Of Different Local Varieties Of Banana (Musa Sp.) - POONGODI,; MOHANASUNDARAM,; SIVAKUMAR, KARTHIKEYAN,; SHEELADEVI,; THIRUMALAI,; PENNARASI, (International Journal of Pharma and Bio Sciences, 2012)
This investigation was aimed to evaluate and compare the antioxidant activity of the pulp extracts of nine varieties of banana, viz Kadali, Karpooravalli, Monthan, Nenthiran, Pachainadan, Poovan, Rasthali, Robusta and Sevvazhai. Ethanolic extraction was performed with the pulp of these banana varieties and subjected to in vitro free radical scavenging assays like DPPH, ABTS, hydroxyl and lipid peroxidation inhibition assay. Total antioxidant capacity assay to initially confirm the antioxidant potential was also carried out. The results obtained were analyzed statistically and found that the pulp extracts of all the nine varieties of banana exhibited significant antioxidant activity. Rasthali, Monthan, Sevvazhai, Karpooravalli and Pachainadan showed highest free radical scavenging activity compared to other varieties.